Analyzing multiple-source water usage patterns and affordability in rural Central Appalachia - Dudzinski, Emerald; Ellis, Kimberly; Krometis, Leigh-Anne; Albi, Kate; Cohen, Alasdair (PLOS Water, 2025)
Nearly 500,000 American households lack complete plumbing, and more than 21 million Americans are reliant on public drinking water systems with at least one annual health-based drinking water violation. Rural, low-income, and minority communities are significantly more likely to experience unavailable or unsafe in-home drinking water. Lack of access and distrust of the perceived quality of municipally supplied water are leading an increasing number of Americans to rely instead on less regulated, more expensive, and potentially environmentally detrimental water sources, such as roadside springs and bottled water. Previous research studies have stressed the importance of considering the economic burden of all water-related expenditures, including financial and non-financial water-related costs; however, past examinations of water costs have primarily focused on municipal water supplies. We propose an economic model to consider the full economic burden associated with multiple-source water use by incorporating both direct costs (e.g., utility bills, well maintenance, bottled water purchase, payments for water hauling/delivery) and indirect water-related expenditures (e.g., transportation costs to gather water, productivity lost due to time spent collecting). Using data gathered from household surveys along with the economic model, this study estimates the economic burden from two case studies in rural Central Appalachia with persistent water quality concerns: (1) McDowell County, WV (n = 15) and (2) Letcher and Harlan Counties, KY (n = 9). All surveyed households (n = 24) rely on multiple sources of water to meet their needs, frequently citing their perception of unsafe in-home tap water. Bottled water was the most common choice for drinking water in both settings (92%, n = 24), though roadside spring use was also prevalent in McDowell County, WV (53%, n = 15). The results show that multiple-water source use is associated with a large economic burden. Households reliant primarily on bottled water as their drinking water source spent 10.3% (McDowell County, WV) and 5.3% (Letcher and Harlan Counties, KY) of their respective county’s median household income (MHI) on water-related expenditures. Households reliant primarily on roadside springs as their drinking water source spent 6.4% (McDowell County, WV) of MHI on water-related expenditures. Hence, the majority of participating households (75%, n = 24) spend above the US water affordability threshold of 2% MHI. The application of this economic model highlights substantial water affordability concerns in water-insecure Appalachian communities and provides a foundation for future studies and enhancements.